The effect of work engagement on job satisfaction mediated by organizational commitment in trading companies - Diky Mahendra; Muhamad Ekhsan (Jurnal Mantik, 2023)
The purpose of this study was to determine whether there is an effect of work engagement on job satisfaction mediated by organizational commitment. The object of research at PD. DB Cikarang. The research was conducted using quantitative methods with SEM Smart PLS software as an analytical tool. The number of samples obtained by random sampling technique using the slovin formula amounted to 60 respondents. Data collection is done through using google form in filling out online surveys. The data analysis method used is the R-square test, Bootstrapping, Path Coefficient, and Specific indirect effects. The results of this study indicate that (1) the job satisfaction variable has a significant positive effect on organizational commitment, meaning that if the level of satisfaction in employees is very high, the commitment to the company is also very good. (2) the work engagement variable has a positive and significant effect on job satisfaction, so this explains that the higher the work engagement, the higher the job satisfaction. (3) the work engagement variable has a positive and significant effect on organizational commitment, meaning that the higher the work engagement, the higher the organizational commitment (4) the organizational commitment variable has a positive effect and can mediate work engagement and job satisfaction, it means that the higher the work engagement and job satisfaction, the higher the organizational commitment to the employee's responsibility with the company.